(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the linguo-creative strategies through which an orator constructs and sustains a charismatic image in public speech. The empirical basis consists of two Russian authors — Joseph Brodsky (fragments of the Nobel Lecture, 1987) and Alexander Solzhenitsyn (fragments of the Harvard speech A World Split Apart, 1978). The theoretical framework is based on frame semantics (C. Fillmore), the theory of conceptual metaphor (G. Lakoff, M. Johnson), and the “new rhetoric” (Ch. Perelman, L. Olbrechts-Tyteca). The results section presents a microlinguistic analysis of specific sentences, showing how metaphorical reframing, paradoxical definition, aphoristic compression, gradation, and deictic densification organize the ethos, logos, and pathos of speech. It is shown that charisma is articulated not “psychologically” but discursively — as the effect of the coordinated functioning of cognitive and rhetorical mechanisms. The article examines the linguo-creative strategies through which an orator constructs and sustains a charismatic image in public speech. The empirical basis consists of two Russian authors — Joseph Brodsky (fragments of the Nobel Lecture, 1987) and Alexander Solzhenitsyn (fragments of the Harvard speech A World Split Apart, 1978). The theoretical framework is based on frame semantics (C. Fillmore), the theory of conceptual metaphor (G. Lakoff, M. Johnson), and the “new rhetoric” (Ch. Perelman, L. Olbrechts-Tyteca). The results section presents a microlinguistic analysis of specific sentences, showing how metaphorical reframing, paradoxical definition, aphoristic compression, gradation, and deictic densification organize the ethos, logos, and pathos of speech. It is shown that charisma is articulated not “psychologically” but discursively — as the effect of the coordinated functioning of cognitive and rhetorical mechanisms.